Multimodalidade e representações de amor e gênero no brincar de roda: a performance em Alecrim – brincadeiras cantadas - Santos Júnior, Massilon da Silva Moreira dos (2020)
The role of children in society reverberated by playing has demonstrated the importance of research on the children's universe. However, the number of plays ends up hampering a more detailed study in view of the numerous possibilities that playing provides, thus requiring an analytical approach. In this sense, this work aims to demonstrate, in the context of childhood playful culture (BROUGÈRE, 2016) how multimodality is perceived through playing with nursery rhymes, children's plays of unknown origin and which are part of Brazilian folklore and culture (MARTINS, 2012), and how the representations of love and gender are determined in this game for the production of multiple meanings from the performance (ZUMTHOR, 2000) in the video Alecrim - Brincadeiras Cantadas, from TV UFPB. This research takes nursery rhymes as texts and brings as objectives the understanding of how the performance and multimodal character are determined in playing with nursery rhymes in the context of childhood playful culture, in addition to realizing what semioses are found in playing with nursery rhymes represented and theatricalized in performance in the video, identifying how the representations of love and gender take place in the face of images, movement, the scenic game and the lyrics of nursery rhymes during the performance of the play. For this research, three nursery rhymes of the amorous type were selected in the video corpus because this type of songs denotes the game of insinuation and conquest performed by girls in a more remote time (JURADO FILHO 1985; PIMENTEL; PIMENTEL, 2004), being video fragmented into different levels of film analysis (BALDRY; THIBAULT, 2005; IEDEMA, 2001) and investigated against the theoretical assumptions of the Grammar of Visual Design for moving images (KRESS; VAN LEEUWEN, 2006; VAN LEEUWEN, 2005a). Our results demonstrate that nursery rhymes present a whole multimodal apparatus due to their placement in performance, but that the representations of love and gender go unnoticed in the theatricalization of these plays by the children, even though these issues are strongly portrayed in the lyrics of the songs. Such results show that this playful activity has been played without distinction by boys and girls, and that the current conceptions of playing with nursery rhymes and childhood diverge from those of remote times, with theatricalization as its key point.